"Jaz sem pa mislila, da je kakšen vohun" - Simikič, Alenka (Etnolog. Nova vrsta (Ljubljana), 2003)
Dr. Boris Orel was the first post-war director of the Ethnographic Museum. The article is dedicated to the 100th anniversary of his birth and the 55th anniversary of the start of his first field team's activities. It is an attempt to shed light on the figure of Dr. Boris Orel, his enthusiasm for and love of his work and discipline through an analysis of the work organisation and life of the field team in the third year after the end of the Second World War.
Keywords: Orel, Boris, 1903-1962; Slovenski etnografski muzej; Ljubljana; ethnology; etnologija; ethnography; etnografija; terensko raziskovanje; terenske ekipe; Slovenia; Slovenija